An innovative multilayer wall composed of natural materials: experimental characterization of the thermal properties and comparison with other solutions. (August 2018) - Buratti, Cinzia; Belloni, Elisa; Merli, Francesca; Zanella, Veronica; Robazza, Paolo; Cornaro, Cristina
Abstract: In order to reduce the carbon emissions resulting from buildings construction, some non-conventional materials are emerging, especially the ones of natural origin. In this scenario new building components have been developed as thermal insulating panels such as the ones made of wood, straw, and cork. In the present paper a multi-sheet wall was investigated by analyzing the thermal properties of each layer by means of a new experimental apparatus named Small Hot-Box. The wall is composed from the outside towards the inside by a 'cocciopesto' mortar, a thick layer of straw, a wooden planking, an air interspace of about 5 cm, and a final raw earth plaster, for a total thickness of about 50 cm. Results showed thermal conductivities in accordance to Literature values both for the wood (0.089 W/mK) and for the straw (0.065 W/mK). For the 'cocciopesto' and the earth-based plasters no many Literature data are available: the thermal conductivities are equal to 0.92 and 0.98 W/mK respectively. The total thermal transmittance of the wall was estimated by combining the results and considering the real scale thickness of each layer; it is about 0.15 W/m 2 K.